Výběr a implementace informačního systému - Podzemný, Matěj (Vysoké učení technické v Brně. Fakulta podnikatelská, 2022)
Tato diplomová práce se zabývá výběrem a implementací nového informačního systému na Střední Škole Odry. Cílem této práce je zanalyzovat aktuální stav školy a jejího systému a na základě těchto analýz a požadavků provést výběr a implementaci nového informačního systému. První část diplomové práce je věnována teoretickým východiskům, v druhé části jsou provedeny ony zmíněné analýzy následované samotným návrhem řešení. Součástí návrhového řešení je v závěru i finanční analýza a popsány přínosy tohoto řešení.

This master’s thesis deals with the selection and implementation of a new information system at Odry Secondary School. The aim of this thesis is to analyze the current state of the school and its information system and based on these analyses and requirements to select and implement a new information system. The first part of the thesis is devoted to the theoretical background, in the second part of the thesis the mentioned analyses are performed followed by the actual design of the solution. The design solution is concluded with a financial analysis and the benefits of the solution are described.
Implementation of the information system
Keywords: data; informace; informační systém; analýza; SWOT; rizika; Lewin; PERT; implementace; data; information; information system; analysis; SWOT; risks; Lewin; PERT; implementation